Na Baixa do Sapateiro (Bahia) by Ary Barroso in the interpretation of John Coltrane: The use of the composition as a vehicle for improvisation in modal jazz - Gomes, Luis Felipe (2017)
Analytic study of John Coltrane’s interpretation of the song Na Baixa do Sapateiro (Bahia), composed by Ary Barroso.From phonographic record, we conducteda transcription in which we could observe an adaptation of the composition foruse as improvisation practice linked tomodal jazz, a territory explored by the saxophonist in his career. Firstly, we discussthe political issues that contributed to thediffusion of Brazilian music in the UnitedStates in the 1940s. Next, we address Coltrane’s relation to modal jazz, exposingits characteristics and emphasizing theimportance of George Russel (2001) inthe genesis of said style. Finally, we touch upon matters of performance in regardto the adaptations of the aforementionedcomposition, as well as aspects of the saxophonist’s improvisation. That said, thispaper represents a contribution to improvisation studies, adding to the perspectiveof ethnomusicology and interpretive practices in popular music.